1981
DOI: 10.1111/j.1570-7458.1981.tb03068.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF ABSCISIC ACID ON VITELLOGENESIS IN SARCOPHAGA BULLATA

Abstract: In the carnivorous dipteran Sarcophaga bullata Parker, vitellogenesis was partially inhibited by injection of two doses of 12 μg abscisic acid (ABA), There was no significant difference between injections on day 2 and 4, or on day 4 and 6. Higher and lower doses were less effective, The mixture of isomers inhibited vitellogenesis more than the cis‐trans isomer. ABA had no effect on the total lipid concentration of the haemolymph but it inhibited the sharp increase in total protein concentration of the haemolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
(14 reference statements)
1
3
1
Order By: Relevance
“…et al, 2008). The reduction in Vg expression that we observed is consistent with reduced Vg levels in S. bullata injected with ABA (De Man et al, 1981) and reduced Vg levels reported for malnourished A. aegypti (Shiao et al, 2008). Reduced protein content has been shown to result in smaller follicle size and increased resorption of oocytes (Caroci et al, 2004;Clifton and Noriega, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…et al, 2008). The reduction in Vg expression that we observed is consistent with reduced Vg levels in S. bullata injected with ABA (De Man et al, 1981) and reduced Vg levels reported for malnourished A. aegypti (Shiao et al, 2008). Reduced protein content has been shown to result in smaller follicle size and increased resorption of oocytes (Caroci et al, 2004;Clifton and Noriega, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Further, ABA affected 20E titers on only a single day of larval development (day 6) at the highest concentration of ABA (100 µM), affirming minimal to no effect of ABA on the interacting effects of JH and 20E. Our data contrast with the reported effects of ABA on 20E in adult S. bullata (De Man et al, 1981), suggesting the likely possibility that the effects of ABA vary to some degree across insect species. In D. melanogaster, reduced food seeking behavior is mediated by the overexpression and release of ILP2 and ILP4 (Wu et al, 2005), suggesting that reduced expression of ilps in our ABA treated larvae might be associated with increased food seeking behavior.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…We reasoned that the changes in ilp expression induced by ABA could have an effect on fecundity as observed in Aedes aegypti [49] and based on observations that injections of ABA reduced vitellogenesis in the flesh fly Sarcophaga bullata [50] . However, ABA had no effect on egg laying rate, clutch size, and egg hatch rate relative to unsupplemented control A. stephensi following a single uninfected blood meal (Fig.…”
Section: Resultsmentioning
confidence: 99%